A light bulb moment: an unusual cause of foreign body aspiration in children. (26th August 2015) - Lau, C T; Lan, Lawrence; Wong, Kenneth; Tam, Paul Kwong Hang
Abstract : A 15-month-old girl developed persistent cough with no associated history of foreign body aspiration. Chest X-ray showed a U-shaped radiopaque foreign body, which was initially thought to be a hairpin, in the right main bronchus. Rigid bronchoscopy was performed and the foreign body turned out to be a light-emitting diode (LED) bulb. In this article, we report our experience of LED bulb aspiration in children, with the view to raise the awareness of clinicians about this potentially life-threatening emergency.